Prediction of late left ventricular thrombus formation after ST-elevation myocardial infarction: A cardiovascular magnetic resonance study - Magdalena Holzknecht; Christina Tiller; Ivan Lechner; Fritz Oberhollenzer; Alex Kaser; Martin Reindl; Felix Troger; Mathias Pamminger; Axel Bauer; Bernhard Metzler; Sebastian Johannes Reinstadler; Agnes Mayr (International Journal of Cardiology: Heart & Vasculature, 2025)
Background: Little is known about the prevalence of late left ventricular thrombus (LVT) formation after ST-elevation myocardial infarction (STEMI). Compared with transthoracic echocardiography (TTE), cardiovascular magnetic resonance (CMR) imaging has a much higher sensitivity for LVT detection in patients after acute STEMI. However, routine CMR imaging is currently not integrated in post-STEMI management. We sought to develop a practical risk score for the prediction of late LVT formation after STEMI. Methods and Results: Six hundred and nine patients with STEMI underwent CMR at 3 [IQR:2–4] days and 4.4 [IQR:4.1–4.9] months after primary percutaneous coronary intervention (PCI) for acute STEMI. A LVT was visualized in 37 patients (6.1 %) at baseline CMR and was newly diagnosed in 10 patients (1.6 %) at 4 months follow-up (4FU) CMR and in 4 patients (0.7 %, 60 % false-negative rate of TTE in detecting LVT) by 4FU TTE. A simple clinical risk score including associates of late LVT (left anterior descending artery as culprit vessel and 4FU NT-pro-BNP > 236 ng/l), with a range of 0 to 2 points (median risk score: 1 point) showed a strong and significantly higher area under the curve (0.89, 95 %CI 0.86–0.91; p < 0.001) for LVT prediction at 4FU than each individual risk factor alone (p < 0.001). The sensitivity and specificity of the risk score were 100 % and 77 %, respectively. Conclusions: The proposed risk score may offer preliminary utility in predicting late LVT and could help to identify patients with STEMI in whom CMR for late LVT assessment might be particularly informative. Additional investigation in larger cohorts is warranted to validate the clinical application of the score.